Pendidikan Karakter Anak Berkebutuhan Khusus Pada Anak Tunalaras - Putri, Wina Sagita; Setiani, Desi Fitri (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to explore: 1) the purpose of character education for children with disabilities; 2) factors that influence children with disabilities; 3) character education for children with disabilities. The research method used is Systematic Literature Review (SLR) with six stages. The results of this study indicate that 1) the purpose of character education in children with reasonableness is an effort to help the development of children's souls both physically and mentally, from their natural nature towards a humane and better civilisation; 2) One of the factors affecting children with reasonableness is that they are unable to have good relationships with friends and teachers. The factors that cause it are heredity, damage and the environment; 3) character education in children with tunalaras using teaching methods in children with tunalaras can use habituation methods, lecture methods, demonstration methods, repetition methods, question and answer methods, assessment methods and exemplary methods.